First Report of Alternaria alternata causing leaf spot on fig (Ficus carica L.) in Karbala Province, Iraq - Hameed, Zainab L.; Lahuf, Adnan A. (Journal of Kerbala for Agricultural Sciences, 2022)
Fig is an important tree that is cultivated worldwide including Iraq. During a survey held in 2018 in orchards of Alhusaynia territory, Karbala Province, Iraq, an epidemic leaf spot disease affecting fig trees was observed. Based on morphological appearances and rDNA-ITS sequence analyses, the fungi caused this disease was recognized as Alternaria alternata. To our knowledge, this is the first record of A. alternata causing leaf spot disease on fig trees in Karbala, Iraq.